Steeply dipping basement faults and associated structures of the santander massif, eastern cordillera, colombian andes (1993)
The Santander Massif is a broad basement uplift, limited on both flanks by two major reverse faults. More internal faults, however, though very steeply dipping, are normal faults and limit sedimentary half· grabens. Much of the Neogene fault pattern is inherited from a Jurassic extensional event. The Neogene extensional deformation regime of the massif's internal parts is accounted for by a vertical uplift with an outward directed spread component, due to the fan array of its faults. This model is modified for a narrow, elongated uplift at Malaga, where the space problems created by the heave of a rock volume above downward curved faults have been overcome by the collapse of marginal synclines.